1988
DOI: 10.3382/ps.0670635
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis Muscle Shortening and Rigor Development at Different Locations Within the Broiler Breast

Abstract: Two experiments were conducted to evaluate differences in rigor development that occur as a function of location within the broiler breast muscles, pectoralis major (p. major) and pectoralis minor (p. minor). Three locations were evaluated, corresponding to anterior, middle, and posterior samples taken between the cranial and caudal ends of each muscle. Results of the first experiment indicated that the 1.55-mu sarcomere lengths of hot-boned p. major muscle at the anterior location were significantly shorter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 16 publications
2
17
0
2
Order By: Relevance
“…R-values for meat at both temperatures at 3 hr PM exceeded 1.2. These results are similar to those of Papa and Fletcher (1988). But R-value was not significantly different between the two storage temperatures (p>0.05).…”
Section: Results and Discussion Ph And R-valuesupporting
confidence: 86%
See 1 more Smart Citation
“…R-values for meat at both temperatures at 3 hr PM exceeded 1.2. These results are similar to those of Papa and Fletcher (1988). But R-value was not significantly different between the two storage temperatures (p>0.05).…”
Section: Results and Discussion Ph And R-valuesupporting
confidence: 86%
“…As rigor mortis develops, R-value increases. R-value of broiler pectoralis major reaches 0.95-0.97 in 15-30 min PM, and reaches 1.2-1.3 in 2-4 hr PM (Papa and Fletcher, 1988).…”
Section: Results and Discussion Ph And R-valuementioning
confidence: 84%
“…Isso demonstrou que a -12 o C, aves com maior energia disponível no pectoralis major (PM) aos 15min p.m., sofreram maior encurtamento. PAPA & FLETCHER [14] verificaram a susceptibilidade do PM de frango ao encurtamento p.m. e observaram que houve redução na retenção de água e na maciez, quando as amostras foram submetidas a cocção e ao processamento. LOCKER & HAGYARD [12] descreveram que músculos acometidos de cold shortening resultaram em endurecimento da carne bovina após o cozimento.…”
Section: -Introduçãounclassified
“…This result is consistent with that of Beecher et al (1965), which indicates that red muscles (>40% red fibers) generally have a longer post-rigor sarcomere length than do white muscles (<30% red fibers). Papa and Fletcher (1988) reported that reduced sarcomere lengths resulted in increased shear force in broiler breast muscle.…”
Section: ±001mentioning
confidence: 99%